The histidine decarboxylase model of tic pathophysiology: a new focus on the histamine H3 receptor. (27th March 2019) - Pittenger, Christopher
Abstract : Histamine dysregulation was implicated as a rare cause of Tourette syndrome and other tic disorders a decade ago by a landmark genetic study in a high density family pedigree, which implicated a hypomorphic mutation in the histidine decarboxylase ( Hdc ) gene as a rare but high penetrance genetic cause. Studies in Hdc knockout (KO) mice have confirmed that this mutation causes tic‐relevant behavioural and neurochemical abnormalities that parallel what is seen in patients and thus validate the KO as a potentially informative model of tic pathophysiology. Recent studies have focused on the potential role of the histamine H3 receptor in this model, and by association in tic disorders and related neuropsychiatric conditions. The H3 receptor is up‐regulated in the striatum in Hdc KO mice. As the H3 receptor has constitutive activity in the absence of ligand, this receptor up‐regulation may have significant cellular effects despite the absence of neurotransmitter histamine in these mice. Activation in vivo of H3 receptors in wild type mice regulates signalling in striatal medium spiny neurons (MSNs) that interacts non‐linearly with dopamine receptor signalling. Baseline signalling alterations in MSNs in Hdc KO mice resemble those seen after H3 receptor agonist treatment in wild type animals. H3 receptor agonist treatment in the KOs further accentuates most of these signalling abnormalities and produces behavioural stereotypy. Together, these data suggest the intriguing hypothesis that constitutive signalling by up‐regulated H3 receptors explains many of the molecular and behavioural abnormalities seen in these animals. Linked Articles: This article is part of a themed section on New Uses for 21st Century. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.3/issuetoc